(3GdUOQjIs ((3eMeO bGLGQHhfj s)
(3ChdgG (B:s
(3CeG HYO, deG CdaJ GdbhGYO GdfMhjI hSejJgG HGdQSGdI GdTeSjI s
(3BNQgG (B:s
(3hbO jchf HeYfi GdMb fMh (B"(3cdG Ef GdEfSGf djWZi(B" (3aEf cdG ajg HeYfi GdMb hbO hbY GdEJeGe HGdMb s
(3GdeDda UGMH GdQSGdI GdTeSjI ai GdbhGYO GdMhjIs
(3HgG fXGe GdJYbjHIs
(3HCWQGagG JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs